The Cosmopolitan Virus – Covid-19 Does Not Strike Randomly - Ruud Koopmans (WZB Berlin Social Science Center, 2020)
Highly mobile world citizens were among the first to be infected. Meanwhile, the virus affects everyone - yet not everybody is affected equally.
Keywords: 300; contagious disease; Coronavirus; cosmopolitanism; COVID-19; epidemic; risk; social inequality; world